Seeking artistic transformation elsewhere : microresidencies with case studies from Yogyakarta and Bali, Indonesia - Tengku Kamiliah Tengku Bahdar (2018)
This thesis explores the increasing importance and prominence of artist residencies in relation to broader developments in contemporary art practices that is characterised by an expansion into the field of culture. It begins by first examining the definitions and typologies of residencies, highlighting in particular the microresidence—a type of residence that is small-scale and often artist-run. In looking at the typologies of residencies through its working method, process and outcome, it reveals how particular residencies are structured to support current contemporary art practices that are now more discursive and in which the artwork is increasingly deaestheticised and dematerialised. Of particular interest is how, with the increasingly nomadic practice of artists, the act of traveling and dwelling elsewhere with residencies also provides resident artists with access to spatial, temporal and cultural alterity that is potentially transformative. With data collected through fieldwork and participant observation, microresidences Cemeti Art House in Yogyakarta and Ketemu Project Space in Bali, Indonesia serves as case studies of how a residency programme might structure itself to support discursive practices and the importance placed on sociality. By making visible the production happening in residencies, the thesis hopes to highlight the value of present-day artist residencies not just for artists but also the locality it is embedded in.